Investigation on protalus ramparts in the Swiss Alps - Scapozza, C. (Geographica Helvetica, 2015)
The origin and classification of landforms denominated as "protalus ramparts" in the scientific literature is a problem that is far from being resolved. The main objective of this contribution is to support a permafrost-related definition of protalus ramparts. If we consider the Alpine framework, protalus ramparts are generally very rare landforms; by contrast, the Alpine periglacial belt is characterised by a large diffusion of talus slopes and talus rock glaciers. The investigations carried out in six sites of the Valais Alps (Switzerland) allow eight major "diagnostic criteria" to be presented that help to define protalus ramparts in Alpine environments and that support the permafrost-related genesis of most of them. The major source of controversy is related to the use of the term protalus rampart to designate both a nivo-gravitational landform (also called "pronival ramparts") and a permafrost-related landform. All the considerations presented here allow an active protalus rampart to be defined simply as a (small) active talus rock glacier.